Depressing effect of flocculants on molybdenite flotation. (April 2015) - Castro, S.; Laskowski, J.S.
Highlights: Molybdenite is depressed by anionic polyacrylamides and non-ionic polyethylene oxide. Shear degraded polyacrylamides are strong molybdenite depressants. Shear degraded polyacrylamides lose completely its flocculation ability. Use of flocculants in bulk Cu–Mo concentrate thickener must be avoided. Recycled water may contain residual flocculants detrimental to molybdenite flotation. Abstract: The quality of recycled process water is an important issue in the flotation of Cu–Mo ores. Processing of Cu–Mo ores includes two steps: a bulk flotation where molybdenite is recovered together with Cu sulfides, and a subsequent selective flotation step where molybdenite is separated from depressed copper sulfides. Flocculants are usually employed in the middling thickeners in the copper plant, and in the Cu–Mo bulk concentrate ahead of the molybdenite plant. However, the floatability of molybdenite, similarly to other naturally hydrophobic minerals, is highly sensitive to the presence of both natural and synthetic polymers. In this work flotation tests demonstrate that conventional flocculants, high-molecular weight anionic polyacrylamides (PAM), are strong molybdenite depressants. Low-molecular weight shear degraded polyacrylamides in spite of losing flocculation efficiency maintain depressing ability for molybdenite. Also a non-ionic flocculant, polyethylene oxide (PEO), has been studied in this project. Our results indicate that PEO is an efficient flocculant for molybdenite suspensions in a wide pH range. However, similarly to polyacrylamides, the PEO flocculant also depresses molybdenite flotation.